A New Transcoding Scheme for Scalable Video Coding to H.264/AVC - Zhenyu Wu Zhenyu Wu; Daiying Zhou; Hong Hu Hong Hu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Requests from various video terminals push video servers to equip with scalability for video contents distribution in different ways. Scalable Video Coding (SVC) as the extension of H.264/AVC standard can provide the scalability for video servers by encoding videos into one base layer and several enhancement layers. To enable mobile devices without scalability receive videos at their best extent, converting bit-streams from SVC into H.264/AVC becomes the key technique. Bit-stream rewriting is the simplest way without quality loss. However, rewriting is not a real transcoding scheme, since it needs to modify SVC encoders. This paper proposes a novel transcoding approach to support spatial scalability by minimizing the distortions generated from re-encoding process. The proposed scheme keeps the input bit-streams’ information at maximum and adopts the hybrid upsampling method to do residue scaling, which can reduce the transcoding distortion into minimization. Experimental results demonstrate that the loss of the rate-distortion (RD) performance of the proposed transcoding scheme is better than Full Decoding Re-encoding (FDR) which can get the highest video quality in general sense, by achieving up to 0.9 dB Y-PSNR gain while saving 95%~97% processing time.